Sexual Harassment on The Photocopier Movie 2021: Critical Discourse Analysis - Rena Rensiana Girsang; Andi Muhammad Irawan (English Language and Literature, 2023)
The purpose of this study was to identify discourse topics and discourse strategies that contained sexual harassment contained in the movie “Photocopier” and analyze them using Van Dijk’s theory of critical discourse analysis. This type of research is qualitative research. The data sources are dialogues from the “Photocopier” movie. In this study, Van Dijk’s theory of critical discourse analysis of Positive Self and Negative Other Representation was applied. According to the findings, there are nineteen dialogues including five discourse topics and seven discourse strategies contain sexual harassment. In the movie, the most dominant discourse topics is the women as a sexual objects and in the discourse strategy is the strategy of problematization.